Energy balance in the watershed of Ipê, Northwestern São Paulo State, Brazil. - FEITOSA, D. G. (2016)
The aim of this paper was to assess someparameters related to the energy balance of Ipês watershed, that changed since no sugarcane cultivation in 2006 to 2.164 hectares in 2011, occupying 31% of the catchment area with this important energy crop For the economy and the environment of Brazil.